Network Pharmacology of Ki Encok (Plumbago zeylanica Linn) Plant as A Treatment for Osteoarthritis - Purwoko, Mitayani; Mundijo, Trisnawati; Widyadi, Yoshiko (Chimica et Natura Acta, 2025)
One of the plants in Indonesia used by the community to treat gout or Osteoarthritis (OA) is the Ki Encok plant (Plumbago zeylanica Linn). However, it is currently unknown what active substances play a role in the therapy process for gout or OA and what the pathway is. This study aimed to predict the pharmacological mechanism of the active content of Encok leaves against OA disease. This study used an in silico experimental test. The content of active plant substances was extracted from IMPPAT and KNAPSACK. Then, the target proteins of all these active substances were searched for, including target proteins involved in OA disease, through the GeneCards database. Common targets were then analyzed using the STRING database. Pathways involved in OA therapy by P. zeylanica Linn were analyzed using Gene Ontology. The active substances P. zeylanica plant are 52 components with 163 protein targets. Proteins involved in the pathogenesis of OA were found to be 5,394 proteins. Common targets were found to be 100 proteins. After being analyzed based on degree, the top 10 common targets that may play a role are ALB, TNF, INS, AKT1, TP53, IL6, PPARG, ESR1, HIF1A, and JUN. The active compounds contained in P. zeylanica with target proteins that match OA are D-glucose, vanillic acid, beta-stigmasterol, isoorientin, and lupeol.